Analysis of the Influence of Accounting Information on Stock Price with the Extent of Corporate Social Responsibility Disclosures as a Moderation - Varsha V; Dhanaraj, V.T. (African Journal of Commercial Studies, 2024)
Corporate social responsibility (CSR) is a new dimension because “it opens new work spaces for the accounting discipline and articulates it with transparency, ethics, and the social responsibility of the company towards society as a whole." In this sense, it allows companies to receive only benefits, in social, economic and environmental matters, allowing, through what is reflected in the financial statements, to comply with what is established by the Micro, Small and Medium Enterprises Development Act, 2006 determined by the Ministry of Finance, India, in which it specifies the incentives for MSMEs that are covered by the provisions that it indicates, these being the following incentives: Additional scores in public tenders, Access facilities to credits greater than a certain amount, Access to micro and small business development programs, Promotion of Technological Innovation, and Others that are incorporated in the future by the National Government. In this way, the present study explores compliance with standards, principles, and procedures that regulate the financial, accounting, and tax structure and operation of the company represented by NDR Auto Components Ltd, guiding management to counteract the tax obligations covered by the law. This is why it is intended to argue and document the importance and advances of corporate social responsibility on accounting information, in the use of IFRS, in terms of the management of this new legislation, those that refer to taxes.